2012
DOI: 10.1063/1.3673792
|View full text |Cite
|
Sign up to set email alerts
|

Clusters dissolution of Yb3+ in codoped SiO2-Al2O3-P2O5 glass fiber and its relevance to photodarkening

Abstract: Using a combination of pulse electron paramagnetic resonance and photoluminescence spectroscopy, we demonstrate the major role of phosphorous rather than aluminium in the rare-earth dissolution process, an essential advance in telecommunication and solid laser fields. Our results also provide new insight into the micro-structural origin of the photodarkening process occurring in Yb doped fiber.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
54
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(57 citation statements)
references
References 23 publications
3
54
0
Order By: Relevance
“…These phenomena, due to the ion-ion interactions, lead to undesirable luminescence quenching, thus reducing the performance of the amplifier. At the same time the difficulty of low solubility of rare- [5,6]; their role resides in non-bridging oxygen's formation that benefits better rare-earth ions incorporation. Moreover from a technological point of view physical and chemical deposition techniques such Flame Hydrolysis Deposition (FHD) and Plasma Enhanced Chemical Vapor Deposition (PECVD) have important drawbacks associated to the incorporation of rare earth ions in silicate glasses due to the high process temperatures in the first case [7], and the low vapour pressure of most erbium compounds in the second [8].…”
Section: Introductionmentioning
confidence: 99%
“…These phenomena, due to the ion-ion interactions, lead to undesirable luminescence quenching, thus reducing the performance of the amplifier. At the same time the difficulty of low solubility of rare- [5,6]; their role resides in non-bridging oxygen's formation that benefits better rare-earth ions incorporation. Moreover from a technological point of view physical and chemical deposition techniques such Flame Hydrolysis Deposition (FHD) and Plasma Enhanced Chemical Vapor Deposition (PECVD) have important drawbacks associated to the incorporation of rare earth ions in silicate glasses due to the high process temperatures in the first case [7], and the low vapour pressure of most erbium compounds in the second [8].…”
Section: Introductionmentioning
confidence: 99%
“…P-related centers are also formed by carrier trapping [16] and contribute to the RIA, notably in the visible and near infra-red ranges [17]. However, high P concentrations reduce clustering [13] and also shift the Yb3+ charge transfer (CT) band towards higher energies [18]. Both effects dramatically drop the probability of releasing cooperatively a sufficient energy to reach this shifted CT band, hence the photo-ionization rate.…”
Section: Discussionmentioning
confidence: 99%
“…Phosphorus (P) or aluminium (Al) co-doped YDF are likely to fall within this category. P or Al [13,14] co-doping proved, e.g., to be beneficial against the PD but detrimental to the RD-resistance in the absence of pumping. On one hand, Al-related trapped-hole centers [15] introduce absorption bands that participate in the radiation-induced attenuation (RIA).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that P 5 þ doping improves Yb 3 þ solubility [14,15] and suppresses the photodarkening effect in Yb 3 þ -doped or Yb 3 þ /Al 3 þ co-doped silica glass fiber [11,19,20]. Thus, the great potential of P 5 þ doping in high-power fiber laser has been demonstrated [11,21].…”
Section: Introductionmentioning
confidence: 98%
“…However, rare earth ions have very low solubility in pure silica glass [12,13]. A doping level above the solubility threshold, which is approximately 1000 ppm by weight, will lead to Yb 3 þ clustering or even phase separation [14,15]. Hence, Al 3 þ is widely adopted in silica glass to increase Yb 3 þ solubility [1,16,17] on account of its dispersion effect on rare earth ions [15,18].…”
Section: Introductionmentioning
confidence: 98%